SUBRELATIVISTIC JET HEATING MECHANISMS - Bisnovatyi-Kogan, G. S.; Krivosheyev, Y. M. (Одеські астрономічні публікації, 2011)
Different physical processes, influencing the X-ray jet’s thermal balance are considered. We focus on the problem of possible fast jet cooling via radiative losses. Thus, the contributions of each process to the jet thermal balance are calculated. We investigate the influence of shock wave propagation on jet heating, and the mechanism of jet kinetic energy transformation into heat via Coulomb collisions of jet and corona protons. Quantitative estimates are made for the case of Galactic microquasar SS433 based on previous results of the authors. The only important heating mechanism for this source turned out to be Coulomb collisions.